Volatility at Karachi Stock Exchange (The Pakistan Development Review, 1995)
Frequent “crashes” of the stock market reported during the year 1994 suggest that the Karachi bourse is rapidly converting into a volatile market. This cannot be viewed as a positive sign for this developing market of South Asia. Though heavy fluctuations in stock prices are not an unusual phenomena and it has been observed at almost all big and small exchanges of the world. Focusing on the reasons for such fluctuations is instructive and likely to have important policy implications. Proponents of the efficient market hypothesis argue that changes in stock prices are mainly dependent on the arrival of information regarding the expected returns from the stock. However, Fama (1965), French (1980), and French and Rolls (1986) observed that volatility is to some extent caused by trading itself. Portfolio insurance schemes also have the potential to increase volatility. Brady Commission’s Report provides useful insights into the effect of portfolio insurance schemes. It is interesting to note that many analysts consider the so-called “crashes” of Karachi stock market as a deliberate move to bring down prices. An attempt is made in this study to examine the effect of trading on the volatility of stock prices at Karachi Stock Exchange (KSE). Findings of the study will help understand the mechanism of the rise and fall of stock prices at the Karachi bourse.